2019
DOI: 10.3390/su11051470
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Municipal Masterplans Aimed at Identifying and Fostering Green Infrastructure: A Study Concerning Three Towns of the Metropolitan Area of Cagliari, Italy

Abstract: Building upon a recent piece of research that maps a regional green infrastructure (RGI) in relation to four components (natural value, conservation value, landscape value, and recreational value), this study aims at identifying planning policies that can foster the enhancement of the RGI by increasing one or more of its components at the sub-regional scale. To this end, the RGI suitability map is overlaid with the planning schemes of the municipal masterplans (MMPs) of three towns belonging to the Metropolita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…This second direction can, in principle, be very powerful if linear landscape elements can effectively act as corridors, and are treated as landscape assets and goods to be protected. For instance, vegetated edges along agricultural plots or tree lines along linear infrastructures can foster connectivity [112], as well as enable landscape heterogeneity and, as a consequence, can support larger varieties of species [113][114][115], and facilitate their movement, especially as far as small animals are concerned [116]. Policymakers are, therefore, recommended to include such landscape elements, widely treated as cultural and identity features [117,118], among the goods and assets to be protected against land transformation and to encourage their inclusion in new developments.…”
Section: Discussionmentioning
confidence: 99%
“…This second direction can, in principle, be very powerful if linear landscape elements can effectively act as corridors, and are treated as landscape assets and goods to be protected. For instance, vegetated edges along agricultural plots or tree lines along linear infrastructures can foster connectivity [112], as well as enable landscape heterogeneity and, as a consequence, can support larger varieties of species [113][114][115], and facilitate their movement, especially as far as small animals are concerned [116]. Policymakers are, therefore, recommended to include such landscape elements, widely treated as cultural and identity features [117,118], among the goods and assets to be protected against land transformation and to encourage their inclusion in new developments.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the model is designed to investigate an index score of variables for various characteristics and scales, suggesting the analytical potential to represent the overall well-being state of the city and the availability of GI location choices in a sustainable urban space. Existing GI studies mainly considered geographic and topographic characteristics as key variables [26][27][28][29][30]. In this study, however, publicly accessible descriptive variables-i.e., demographic, climate, environment, and form-specific GI variables-were considered together to enable the overall efficiency improvement of urban elements, including residents.…”
Section: Discussionmentioning
confidence: 99%
“…Zhou and Wu [29] attempted to distribute the Green Land of Hekou City, China, by matching the demand for rust and topographical characteristics. Lai et al [30] identified the relationship between land use and spatial identification by presenting a plan to implement GIs in three areas near Cagliari, Italy.…”
Section: Introductionmentioning
confidence: 99%
“…According to Cortinovis and Geneletti (2018) and Lai et al (2019) [13,14], the integration of green areas (including green infrastructures) in urban planning processes can contribute to provide ecosystem services and benefits for humankind, including adaptation to climate change solutions [15]. Therefore, a proper understanding of the usefulness of green infrastructures for enhancing environmental quality is both theoretically and practically relevant to local urban planners [16].…”
Section: Introductionmentioning
confidence: 99%